2002
DOI: 10.1177/074171302400448618
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Contributions of Adult Learning to Community: A Social Capital Perspective

Abstract: As an explanatory concept that relates skills and knowledge to economic outcomes, "human capital" has dominated for decades. Skills and knowledge are certainly central attributes of a learning society. Given the limitations of economy as a proxy for social well-being, however, two outstanding questions about the impact of adult learning on community linger: What are the multiple impacts of adult learning on community? How do these occur? To address these questions adequately, the theoretical construct of socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 20 publications
0
68
0
3
Order By: Relevance
“…The availability of social capital to individuals and groups depends on the quality of the interactions and the knowledge and identity resources, which are inherent in the participants in the interactions (Balatti & Falk, 2001). The social capital developed through such interactions facilitates leaming and use of skills and knowledge and 'promotes active and sustainable leaming' (Falk, 2000, p. 2).…”
Section: Charles: Willing To Join In and Be Part Ofa Teammentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of social capital to individuals and groups depends on the quality of the interactions and the knowledge and identity resources, which are inherent in the participants in the interactions (Balatti & Falk, 2001). The social capital developed through such interactions facilitates leaming and use of skills and knowledge and 'promotes active and sustainable leaming' (Falk, 2000, p. 2).…”
Section: Charles: Willing To Join In and Be Part Ofa Teammentioning
confidence: 99%
“…Learning, either formal or informal, has been identified by many authors (Balatti & Falk, 2001;Falk, 2000;Falk & Kilpatrick, 1999;Field & Schuller, 1997;Schuller & Field, 1998) as a social capital indicator that results from learning interactions. For some Community Choir members, learning is 'personal growth' (Isabella).…”
Section: Learningmentioning
confidence: 99%
“…Research into adult enrollment patterns has evolved from identifying adults' reasons for enrolling in learning opportunities (Houle, 1961;Johnstone & Rivera, 1965) to examining the social, environmental, situational, and institutional factors that infl uence enrollment (Balatti & Falk, 2002;Cross, 1981;Kilpatrick, Field, & Falk, 2003;Park & Choi, 2009;Smart & Pascarella, 1987;Stein & Wanstreet, 2006;Yang, Blunt, & Butler, 1994). Johnstone and Rivera (1965) suggested that the foundation for adult participation was to improve one's occupational standing by improving present performance or seeking learning for a new occupation.…”
Section: Overview Of Enrollment Researchmentioning
confidence: 99%
“…Le financement de la formation continue, dans l'ensemble des réseaux -institutions d'enseignement ; entreprises ; réseaux associatifs -demeurera toujours une réalité complexe et plurielle (ministère de l 'Éducation, 2004 ;Balatti, 2002 ;OCDE, 2002OCDE, , 2000bBélanger et Bochinek, 2000 ;Carr-Hill, 1999 ;Heidemann, 1996). La formation continue collégiale n'y fait pas exception en raison d'une part de la diversité des sources non gouvernementales, d'autre part de la multiplicité des sources gouvernementales, qu'il s'agisse du ministère de l'Éducation, bien sûr, mais aussi du ministère de l'Emploi, de l'Immigration, de l'Agriculture, de l'Industrie, de la Justice, etc.…”
Section: Les Obstacles Financiers Et Réglementairesunclassified